Do Educator Performance Incentives Help Students? Evidence from the Teacher Incentive Fund National Evaluation - Speroni, Cecilia; Wellington, Alison; Burkander, Paul; Chiang, Hanley; Herrmann, Mariesa; Hallgren, Kristin (Journal of Labor Economics, 2020)
This paper presents findings from a national experimental evaluation of performance bonuses funded by the Teacher Incentive Fund grant program. The study finds no robust evidence of positive impacts of bonuses on student achievement, although some specifications suggest a small positive effect that compares favorably with other education interventions. When controlling for covariates, we find that offering bonuses of an average yearly cost of $100 per student had a small significant impact of about 0.04 standard deviations. However, these impacts are smaller (0.01 standard deviations) and become insignificant when not controlling for covariates or using an alternative method of inference.